Cell division of Giardia intestinalis: assembly and disassembly of the adhesive disc, and the cytokinesis - Tůmová, Pavla; Kulda, Jaroslav; Nohýnková, Eva (Cell motility and the cytoskeleton, 2007)
Trophozoites of Giardia are equipped with a special organelle of attachment, essential for parasite survival and pathogenicity, the ventral disc. Although its basic structure is well established, its reorganization and assembly during cell replication is poorly understood. We addressed some of these problems with aid of conventional, confocal and electron microscopy. We found that dividing Giardia alternates attached and free swimming phases in accordance with functional competence of the parent or newly assembled discs. The division started in attached cells by detachment of the disc microtubules from basal bodies. Shortening and eventual loss of the giardin microribbons, and unfolding of the microtubular layer resulting in collapse of the disc chamber and parasite detachment underlined gradual disassembly of the parent disc skeleton. Two daughter discs assembled on the dorsal side of the attached cell, with their ventral sides exposed on the parent cell surface and their microtubular skeletons growing in counter-clockwise direction. A depression between the assembling discs marked the cleavage plane. The splitting continued during the free-swimming phase with ventral-ventral axial symmetry in a plane of the daughter discs. Finally, the daughter cells with fully developed discs but still connected tail to tail by a cytoplasmic bridge, attached to a substrate and terminated the division by a process resembling adhesion-dependent cytokinesis. The mode of assembly of the daughter discs and plane of the division is compatible with maintenance of the left-right asymmetry of the Giardia cytoskeleton in progeny, which cannot be satisfactorily explained by alternative models proposed so far.
Keywords: Microscopy, Electron, Scanning; fluorescenční mikroskopie; Cell Nucleus Division; Microscopy, Fluorescence; mikroskopie elektronová rastrovací; Flagella; buněčné dělení; Microtubules; cytokineze; Cell Division; transmisní elektronová mikroskopie; flagella; Giardia lamblia; mikrotubuly; zvířata; Trophozoites; Microscopy, Electron, Transmission; dělení bunečného jádra; Cytokinesis; trofozoiti; Animals